(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The dynamic nature of human capital management practice has witnessed major changes in the recent decades. This paper presents various perfectives that manifest a trend in institutional systems, their meaning and its subsequent effect on individual and performance. The study proposed that management support would mediate the relationship between human capital management practice and performance. Research design was descriptive survey. Target population was Egerton University employees; 467 teaching staff, 1,533 non-teaching staff and 85 managers. Purposive sampling; stratified random sampling and simple random sampling were used to arrive at a sample size of 210. A questionnaire with reliability coefficient alpha of 0.754, 0.0731 and 0.789 respectively was completed by the staff. Both descriptive and inferential statistics was used to analyze the data at a significant level of alpha (a) equal to 0.05; with the aid of the Statistical Package for Social Science (SPSS) version 17computer software. The results revealed that, various management practice affect performance. Using Multiple Regression the factors were ordered according to their strength. From the model R= 0.985 and R2=0.969. Corporate culture had largest contribution 44.5% with Beta 0.399. From the findings all factors of study accounted for 97% to the total variability in performance. The study found that 90% of the managers agreed that they support performance. The study recommends the institution to have a policy that emphasize on everyone training either (in or out) as a priority. Training modify attitude, knowledge base, skills, behavior through work experience to achieve effective performance.